Magic, Science and Religion in Social Anthropology. From Tylor to Levi-Strauss - Apud, Ismael (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The following study aims to explore the modern anthropological discourse on religion and its practices (myths, rituals, magic), describing how was built such notion in opposition to the scientific knowledge (and therefore the anthropological knowledge too), and what cultural and psychological concepts are involved in it. In a cut of what would otherwise have been overwhelming, the decision went to address the issue from the classic filiation Tylor-Frazer- Durkheim, Malinowski, Levi-Strauss. A positivist conception is the basic line of argument; an evolutionary discourse which concieves an historical development, and a “ethnocentric” supremacy of Western culture.
Keywords: religion; social anthropology; science; magic